THE COLLABORATIONS BETWEEN TURKEY AND THE U.S IN THE ESTABLISHMENT OF â€œISIS FREE ZONEâ€ IN TURKISH-SYRIAN BORDERS - Rifka Annisa (HI 15 UMY 412, 2015)
*412 This study tries to elaborate the reason behind the change of the Turkey action against ISIS and its decision to join on the U.S led-coalition by involving in military intervention. This study also analyses the foreign policy of Turkey which named as â€œZero problem with neighborâ€ policy to elaborate Turkey and its neighbor relations, especially with Syria. Since they have fluctuate relations and it being more complicated because of the rise of ISIS. In international relations study, the change of Turkeyâ€™s behavior to ISIS is related to foreign policy model, which is rational choice, which will explain the best reason of Turkey to finally using military intervention to fight against ISIS. Moreover, the theory of securitization from Barry Buzan can elaborate the speculation behind another purpose of Turkey to fight against ISIS. The result of the study shows that based on rational choice model of foreign policy Turkey is betrayed its â€œzero-problem-with-neighborâ€ policy to protect its domestic security from the external threats. However, the securitization idea shows that Turkey has another purpose in conducting military intervention. It is not only to overthrow ISIS, but also to overthrow Kurdish and Bashar Al-Assad regime